More natural gas for climate protection? Opportunities and risks of an expanded gas strategy for the European energy supply - Jens Hobohm (Stiftung Wissenschaft und Politik (SWP), 2009)
For the foreseeable future the European energy supply will continue to depend on fossil energy carriers. In that context, natural gas has the potential to contribute to saving CO2 emissions. According to this study, an increased utilization of natural gas could avoid approximately 85 million tons of CO2 emissions throughout Europe in the long term. The study shows that an expansion of the natural gas share would be a responsible step towards securing a reliable and competitive energy supply. In the heat markets, 20 percent of fuel oil and 15 percent of solid fuels should be substituted by gas; and 25 percent of European vehicles should be converted to natural gas. However, the study does not support an expansion of natural gas utilization in power generation.The implementation of a European gas strategy should mainly take into account the following five aspects:1. The EU should increase energy efficiency - as announced - by 20% in relation to the baseline development. 2. Given the reduced European natural gas production, Europe needs access to new gas sources. The EU should continue to pursue the Nabucco project and, in addition to Central Asian gas sources, analyze other supply options (Iran, Iraq). 3. The infrastructure required for the import of liquefied natural gas (LNG) should be extended, preferably also at a location in Germany and / or Poland. 4. Biogas can contribute to a continued decrease of CO2 emissions and to a reduction of the European import dependence. Europe should direct its biomass promotion - to a larger extent - towards biogas. 5. Underground storage of natural gas is an efficient means of ensuring the security of supply. However, strategic reservoirs require a thorough cost-benefit-analysis and an efficient mechanism for supplying reserves in case of an emergency - also across national boarders
Keywords: 320; Europäische Union; Energieerzeugung